High Genetic Heterogeneity in Chinese Patients With Waardenburg Syndrome Revealed by Next-Generation Sequencing - Zhang, Sen; Xu, Hongen; Tian, Yongan; Liu, Danhua; Hou, Xinyue; Zeng, Beiping; Chen, Bei; Liu, Huanfei; Li, Ruijun; Li, Xiaohua; Zuo, Bin; Tang, Ryan; et al. (Frontiers in Genetics, 2021)
Objective: This study aimed to explore the genetic causes of probands who were diagnosed with Waardenburg syndrome (WS) or congenital sensorineural hearing loss. Methods: A detailed physical and audiological examinations were carried out to make an accurate diagnosis of 14 patients from seven unrelated families. We performed whole-exome sequencing (WES) in probands to detect the potential genetic causes and further validated them by Sanger sequencing in the probands and their family members. Results: The genetic causes for all 14 patients with Waardenburg syndrome or congenital sensorineural hearing loss were identified. A total of seven heterozygous variants including c.1459C>T, c.123del, and c.959-409_1173+3402del of PAX3 gene (NM_181459.4), c.198_262del and c.529_556del of SOX10 gene (NM_006941.4), and c.731G>A and c.970dup of MITF gene (NM_000248.3) were found for the first time. Of these mutations, we had confirmed two (c.1459C>T and c.970dup) are de novo by Sanger sequencing of variants in the probands and their parents. Conclusion: We revealed a total of seven novel mutations in PAX3, SOX10, and MITF, which underlie the pathogenesis of WS. The clinical and genetic characterization of these families with WS elucidated high heterogeneity in Chinese patients with Waardenburg syndrome. This study expands the database of PAX3, SOX10, and MITF mutations and improves our understanding of the causes of WS.